Fabrication of miniature foldable storage rack / Mohamad Faiz Mohd Shahrul Munir - Mohd Shahrul Munir, Mohamad Faiz (2022)
A storage rack can assist a range of human activities in daily life. The purpose of a rack is to conserve space by storing goods and items upright for short or lengthy periods. The issue constantly encountered is that storage racks consume an excessive amount of space. While the rack is not used, this will be a major problem for individuals, particularly those who live in homes or crowded places. Therefore, the objective of this project is to create a rack with a folding system, generally known as a miniature foldable storage rack. This rack will be equipped with a folding technology that will allow for significant space savings, particularly in tiny spaces. Several strategies have been applied to ensure the project's success. To begin, research storage racks, produce several designs, choose the best one, and finally, execute the fabrication process. Without a doubt, numerous problems must be overcome for this project to succeed; hence, solutions must be identified to secure the project's success. The most important factor is that discussions with supervisors, engineer assistance, and friends are essential for completing this project. To sum itall up, this project must be successful to benefit individuals and enhance the quality of life.